2022
DOI: 10.2478/cttr-2022-0017
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Formation and Transfer in Open- and Closed-Ended Heated Tobacco Products

Abstract: Summary A lit cigarette forms a positive and negative pressure zone by a puff with respect to the position of its paper burn line. Smoke aerosols generated from the two zones are then pulled through the rod under the puff to form the mainstream smoke. This phenomenon is fundamental to the thermophysics and the resultant chemical composition of the mainstream smoke. In this study, we created two different airflow pathways inside a heated tobacco rod by a puff, and investigated the differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In short, the HTP-A airflow pathway (Figure 1A) was from the perforation on the hollow acetate tube because the tobacco end of the heating device was completely sealed. The HTP-B airflow pathway (Figure 1B) was from the tobacco end (8,9). The working mechanism behind the aerosol formation and transfer for the close-end HTP-A has been described before (8,9).…”
Section: The Heating Devices and Tobacco Sticksmentioning
confidence: 91%
See 2 more Smart Citations
“…In short, the HTP-A airflow pathway (Figure 1A) was from the perforation on the hollow acetate tube because the tobacco end of the heating device was completely sealed. The HTP-B airflow pathway (Figure 1B) was from the tobacco end (8,9). The working mechanism behind the aerosol formation and transfer for the close-end HTP-A has been described before (8,9).…”
Section: The Heating Devices and Tobacco Sticksmentioning
confidence: 91%
“…The air flow design of HTP-A and HTP-B is schematically shown in Figure 1 (8,9). In short, the HTP-A airflow pathway (Figure 1A) was from the perforation on the hollow acetate tube because the tobacco end of the heating device was completely sealed.…”
Section: The Heating Devices and Tobacco Sticksmentioning
confidence: 99%
See 1 more Smart Citation
“…Areas discussed include harmful and potentially harmful constituents (HPHCs), markers of combustion, toxicological risk exposure and health/cancer risk assessment, radioactivity, and nicotine stereochemistry. With respect to the articles identified that described chemical analyses of HTPs, articles or portions of their results were excluded from detailed discussion in this section of the review if they did not detail a direct quantitative comparison between the HTP(s) under investigation and other nicotine-or tobacco-containing products such as cigarettes and/or EVPs (i.e., quantitative data were reported solely for the HTP(s) investigated) [20][21][22][23][24]; only provided an analysis of chemical constituents present in consumables or only provided an analysis of emissions released by consumables using an experimental methodology which did not involve use of the consumable combined with the operation of the associated handheld device as intended by the manufacturer (i.e. creating an exposure scenario different from that of real-world product use) [25][26][27][28][29][30][31][32]; only provided an analysis of nicotine levels present in HTP aerosol and mainstream cigarette smoke without further detail [33].…”
Section: Aerosol Chemistrymentioning
confidence: 99%
“…In addition to pyrolysis temperature, oxygen, as one of the three major elements of combustion, is also decisive in controlling combustion. Based on the creation of a tobacco matrix low-oxygen pyrolysis environment and the establishing of a unique smoke extraction method, NSC has been constructed by B. LI et al (18) to ensure that the tobacco is heated rather than ignited, NSC is a label of the noveldesigned airflow pathway of heated tobacco products. Through the coordination of cigarettes and handheld devices, oxygen (or air) will not flow through the tobacco section during the main aerosol formation and transfer process, thus the aerosol generation mechanism for NSC is fundamentally different from the current heating tobacco products, especially the pyrolysis atmosphere and the airflow pathway.…”
Section: Introductionmentioning
confidence: 99%